Implementation Effectiveness Law Number 4 Of 1996 Concerning Rights Of Dependents Case Study: Registration Of Rights Of Dependents In Pangkep Regency - Amiruddin Amiruddin (Green Publisher Indonesia, 2024)
This study is intended to analyze the implementation of registration of dependent rights in Pangkep Regency, for this reason, several variables have been determined as factors causing the effectiveness of the implementation of registration of dependent rights. This research is a research of Normative Law (Normative Juridical) and sociological (empirical) legal research. Empirical research was conducted on 50 respondents consisting of dependent rights holders or creditors in Pangkep Regency and also taken from the population which is the source in the implementation of registration of dependent rights, namely the Head of the Pangkep Regency Defense Office and PPAT Notaries who entered the research area. The empirical data is analyzed using frequency distribution. In addition to respondents as a source of data as mentioned above, the author also obtained data from the land map office of Pangkep Regency. The results showed that the implementation of registration of dependent rights has not been carried out in accordance with applicable regulations. It can be proven that there are still dependent rights that are submitted for more than 7 (seven) working days, and there are even credits that are not tied to dependent rights. In the implementation of registration of dependent rights in the future, it is recommended to improve the quality and quantity of human resources with training and mental education to be honest, fair and devoted to God Almighty.